Preparation, structural and temperature dependence of optical property of ZnO nanostructures on seeded porous silicon / Kevin Alvin Eswar - Eswar, Kevin Alvin (2014)
In this work, ZnO nanostructures were grown on seeded porous Silicon (PSi) template. There were two stages in this study; the preparation of seeded PSi template in the first stage and the deposition of ZnO nanostructures on seeded PSi in the second stages. The first stage was involved the preparation of PSi by using electrochemical etching method with current density of 20 mA/cm2 for 20 minutes. Then, the PSi was seeded by nanostructured ZnO films using spin coating method. In this stage, effect of precursor molarity and post-annealing temperature were studied using FESEM, AFM, and PL spectrometer. The FESEM images revealed that the seeded PSi was composed of ZnO nanoparticles. Low average surface roughness at molarity of 0.15 M and postannealing temperature of 500 °C shows the uniformity of particle size on the PSi surface. Besides, three distinct peaks are appeared related to ZnO nanoparticles, ZnO defects and PSi surface in PL spectra. In the second stage, ZnO nanostructures were grown on seeded PSi via hydrothermal immersion method. The FESEM, XRD, and PL spectrometer were used to study the effect of precursor molarity and postannealing temperature